2021
DOI: 10.12659/ajcr.931376
|View full text |Cite
|
Sign up to set email alerts
|

Convexal Subarachnoid Hemorrhage Caused by Infective Endocarditis in a Patient with Advanced Human Immunodeficiency Virus (HIV): The Culprits and Bystanders

Abstract: Patient: Male, 52-year-old Final Diagnosis: Infective endocarditis • ischemic stroke • subarachnoid hemorrhage Symptoms: Altered mental status • cough • generalized weakness • shortness of breath Medication: Vancomycin and piperacillin-tazobactam Clinical Procedure: — Specialty: Neurology Objective: Rare disease Background: Convexal subarachnoid hemorrhage (cSAH), a rare form of non-aneurysmal subar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the specific mechanism by which IE causes cSAH is not well understood, several previous studies have revealed that cSAH is associated with IE. [21][22][23] In a retrospective study including 240 IE patients, Boukobza et al reported 31 IE cases (13%) with complicated cSAH that frequently occurred in middle-aged patients. They also reported that the majority of causative pathogens were Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanism by which IE causes cSAH is not well understood, several previous studies have revealed that cSAH is associated with IE. [21][22][23] In a retrospective study including 240 IE patients, Boukobza et al reported 31 IE cases (13%) with complicated cSAH that frequently occurred in middle-aged patients. They also reported that the majority of causative pathogens were Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports of viral infections and nonaneurysmal SAH have been associated with COVID-19 caused by SARS-CoV-2,[ 1 - 4 , 6 , 7 , 9 , 12 , 16 , 17 , 23 , 24 ] while some have been associated with other viruses including human immunodeficiency virus, herpes simplex virus, Epstein–Barr virus, Jamestown Canyon virus, and varicella zoster virus. [ 10 , 15 , 21 , 25 - 27 ] Interestingly, there have been no reports of nonaneurysmal SAH caused by coronaviruses other than SARS-CoV-2, such as severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1 or simply SARS-CoV) and Middle East respiratory syndrome coronavirus. As such, the true affinity of SARS-CoV-2 with cerebral vessels remains unknown in spite of an increasing number of reported cases.…”
Section: Discussionmentioning
confidence: 99%